Enhancements of Positioning for IoT Devices - Odetalla,Hatem; Tian,Guoda (2018)
The aim of this thesis work is to find novel method(s), which enhance the performance of the existing Observed Time Difference of Arrival (OTDOA) positioning technique for Internet of Thing (IoT) devices introduced in Third Generation Partnership Project (3GPP) standard release 14. In this thesis work, NarrowBand IoT (NB-IoT) positioning is considered as the baseline. The scope includes the investigation on positioning reference signal (PRS), including modifying/replacing the current sequence generation by mathematical derivations, and modifying PRS configuration (e.g. increasing the density, new time/frequency resource grid). Moreover, different correlator designs at the receiver side (either operating in time or frequency domain) have been analyzed in terms of performance and complexity. In addition, we also investigate the impact of PRS transmission extension either in time domain by sending multiple subframes or in frequency domain by utilizing more spectrum resources (using more Physical Resource Blocks(PRBs)). Our results show that the current NB-IoT PRS resource mapping is already well designed. The newly suggested sequences and resource time/frequency grids influence the correlation properties which in turn affect the positioning accuracies. Increasing the number of resources for PRS transmission in time/frequency results in positioning accuracy improvements. Different sequences for PRS can lead to performance improvements with the cost of implementation complexity, and design flexibility. In addition, optimizing the original gold sequence shows a consistent good performance gain.
Keywords: Internet of Things; IoT; NB-IoT; Narrowband IoT; Positioning; OTDOA; PRS; Positioning Reference Signal